Permanência e Evasão na Educação a Distância: uma análise dos cursos subsequentes do IFSULDEMINAS Campus Muzambinho - Gomes, Simone Aparecida (Universidade Federal de São Carlos, 2018)
The creation of the Federal Institutes, expanding their campuses and the increase in the supply of vacancies of distance education has provided the democratization of access to education. However, high rates of evasion are observed by those institutions, a problem that causes economic losses. In the face of this reality, this study sought to investigate what are the rates of evasion in the institution and to identify the factors that contribute to the permanence and circumvention of technical courses students following the distance offered by the Federal Institute of Education, science and technology of southern Minas Gerais-campus Muzambinho. The sample analysed was subsequent courses offered students in the distance at the polo capital of Alfenas. The obtained results demonstrated that the factors that contribute to the permanence are the support of the family and the professional recognition and the factors that contribute to the avoidance are the lack of face-to-face lessons, the difficulty of performing stage, the difficulty to understand the contents and to reconcile work with their studies.
Permanence and Avoidance in distance education: an analysis of the subsequent courses of IFSULDEMINAS Campus Muzambinho
Keywords: Educação à distância; Permanência e êxito; Cursos técnicos; Educação profissional; Distance education; Permanence and success; Technical courses; Professional; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS